2006
DOI: 10.1103/physrevd.74.084001
|View full text |Cite
|
Sign up to set email alerts
|

Complete classification of purely magnetic, nonrotating, nonaccelerating perfect fluids

Abstract: Recently the class of purely magnetic non-rotating dust spacetimes has been shown to be empty (Wylleman, Class. Quant. Grav. 23, 2727). It turns out that purely magnetic rotating dust models are subject to severe integrability conditions as well. One of the consequences of the present paper is that also rotating dust cannot be purely magnetic when it is of Petrov type D or when it has a vanishing spatial gradient of the energy density. For purely magnetic and non-rotating perfect fluids on the other hand, whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 50 publications
(112 reference statements)
1
52
0
Order By: Relevance
“…Note however that, by contrast with the latter, these are not the only independent scalar invariants one can construct from C αβµν ; there are also two cubic invariants, see e.g. [32,42,29,41,74,44].…”
Section: Linear Gravitoelectromagnetismmentioning
confidence: 99%
See 1 more Smart Citation
“…Note however that, by contrast with the latter, these are not the only independent scalar invariants one can construct from C αβµν ; there are also two cubic invariants, see e.g. [32,42,29,41,74,44].…”
Section: Linear Gravitoelectromagnetismmentioning
confidence: 99%
“…6 we briefly review the formal analogies between the electric (E αβ ) and magnetic (H αβ ) parts of the Weyl tensor, and the electric (E α ) and magnetic (B α ) fields, e.g. [31,32,33,34,35,36,37,38,39,40,41,42,75]. One of its interesting results is that in the case of vacuum, in the linear regime, one obtains a set of equations formally similar to Maxwell's equations in a Lorentz frame, only with the gravitational tidal tensors (E ij = E ij , H ij = H ij ) in place of E α and B α .…”
Section: Introductionmentioning
confidence: 99%
“…As stated in the previous section, if ∂ w k = 0 ⇒ a x = 0, then, by a theorem due to Wylleman and Van den Bergh [34], a unique PMpf is obtained. The solution set for the WVL PMpf is…”
Section: Pmaf Generalizations Of the Wvl Spacetimementioning
confidence: 78%
“…It is shown that there are two PMpf spacetimes that have related windmill PMaf spacetimes. One of these is the PMpf solution independently found by the present authors [34] (henceforth, referred to as the WVL spacetime), and the other is given by a general solution to the confluent hypergeometric equation by Kummer's functions. The spatial gradient of the energy-density function and the 4-acceleration vector are both 0 for the former spacetime while non-zero for the latter.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation